Battlefield cyber : how China and Russia are undermining our democracy and national security - McLaughlin, Michael G.; Holstein, William J. (Prometheus Books, 2023)
"The United States is being bombarded with cyber-attacks. From the surge in ransomware groups targeting critical infrastructure to nation states compromising the software supply chain and corporate email servers, malicious cyber activities have reached an all-time high. Russia attracts the most attention, but China is vastly more sophisticated. They have a common interest in exploiting the openness of the Internet and social media-and our democracy-to erode confidence in our institutions and to exacerbate our societal rifts to prevent us from mounting an effective response. Halting this digital aggression will require Americans to undertake sweeping changes in how we educate, organize and protect ourselves and to ask difficult questions about how vulnerable our largest technology giants are"--